EXPLORING THE ROLE OF GLUTAMINE IN PREVENTING RADIATION-INDUCED ORAL CANCER: A COMPREHENSIVE REVIEW - SHRI, R. V. DEEPIKAA; BABU, N. ARAVINDHA; MASTHAN, K.M.K.; C, RAMYA; S N, VITHIYA SRI (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Radiation therapy is a cornerstone in the treatment of oral cancers, but it often leads to significant side effects, notably radiation-induced oral mucositis. This condition, marked by painful inflammation and ulceration of the oral mucosa, can severely impact a patient’s quality of life and complicate ongoing cancer treatment. Glutamine, an amino acid known for its role in cellular metabolism and mucosal health, has been documented for its efficacy in reducing radiation-induced mucositis. This review explores the potential of glutamine not only in mitigating mucositis but also in preventing or managing radiation-induced oral cancer. We analyze current research on glutamine’s mechanisms of action, including its role in cellular repair, immune support, and mucosal barrier maintenance. We also review clinical evidence that supports glutamine’s use in managing mucositis and examine emerging insights into its potential benefits for preventing or managing oral cancer. The review highlights the need for further investigation into glutamine’s broader role in cancer treatment and emphasizes its potential to enhance patient outcomes and treatment tolerability. By integrating findings from various studies, this review aims to provide a comprehensive understanding of how glutamine could contribute to improved cancer care and to identify areas where additional research could optimize its application in preventing and managing radiation-induced oral cancer.